Researching Indonesian students’ attitude towards foreign language - Marwan, Ardi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
Foreign language attitude plays a significant role in enhancing one’s motivation to learn a particular foreign language. This study aims to obtain an understanding of Indonesian students’ attitudes toward the Japanese language. The data were collected from 160 students learning Japanese. The Foreign Language Attitude Questionnaire (FLAQ), originally developed by Pierson et al. (1980), was used in this study. In addition, attitude factors identified by Pennington and Yu (1994) based on the results of FLAQ factor analysis were incorporated into the current research. The findings indicate that the majority of students showed positive attitudes toward the Japanese language, with no negative orientation toward the language and its culture. The study also found no significant differences in attitudes toward the Japanese language between male and female students (p > .05). Both male and female students responded positively to Japanese language learning and use.